Edukasi Pentingnya Diet Cairan dan Nutrisi pada Penderita Gagal Ginjal Kronik yang Menjalani Terapi Hemodialisis - Safruddin S; Akbar Asfar; Rahmat Hidayat; Sulhan S; Yesenia Faradillah; Fatma Jama; Masnaidah M (Idea Pengabdian Masyarakat, 2022)
End-stage renal disease is a clinical condition characterized by progressive and irreversible renal failure. End-stage renal failure should require appropriate renal replacement therapy, transplantation or dialysis. The incidence of chronic disease continues to increase, as well as chronic kidney failure patients undergoing dialysis. The importance of regulating fluid and food intake because it can affect the addition of Interdialytic Weight Gain (IDWG). The problem with Partners is that patients who undergo hemodialysis therapy experience weight gain of more than 3 kg and even more than 4 kg. The results of interviews with patients undergoing hemodialysis therapy said that they had not adhered to the fluid intake programmed for them, and there were still many who had not been able to carry out a proper nutritional diet including nutrition. The method used in the service activities is by Lectures/counseling, discussion and question and answer. The results of the service showed that this service activity ran smoothly, so that the participants could follow the series to the end. The result of this activity was an increase in understanding from the pre-test evaluation then post-test there was an increase in participants' understanding of the importance of fluid and nutritional diet in patients.